2020
DOI: 10.1080/23311983.2020.1723831
|View full text |Cite
|
Sign up to set email alerts
|

Afghan undergraduate students’ attitudes towards learning English

Abstract: The study aims to investigate the cognitive, affective, and behavioral attitudes of Afghan students towards learning English. It also studies the differences in the attitudes of the students by their demographic profile, i.e., gender, age, first language, field of study, access to the Internet, and English learning experience in English language centers. The data were collected from 210 randomly selected students from Takhar University through a questionnaire with 30 close-ended items. The data were analyzed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
30
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 25 publications
8
30
1
Order By: Relevance
“…The analysis of the data revealed that the attitude of the Afghan undergraduate EFL leaners towards the importance of learning idioms was very positive. This result is in line with the findings of the studies carried out by Orfan (2020), Al-Houti and Aldaihani 2018, Ababneh (2016) and Tadayyon and Ketabi (2014). However, it contradicts the results of the studies by Abidin et al (2012) and Al-Zahrani (2008) who found that EFL learners carried negative attitudes towards learning English.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The analysis of the data revealed that the attitude of the Afghan undergraduate EFL leaners towards the importance of learning idioms was very positive. This result is in line with the findings of the studies carried out by Orfan (2020), Al-Houti and Aldaihani 2018, Ababneh (2016) and Tadayyon and Ketabi (2014). However, it contradicts the results of the studies by Abidin et al (2012) and Al-Zahrani (2008) who found that EFL learners carried negative attitudes towards learning English.…”
Section: Discussionsupporting
confidence: 73%
“…English is taught and learned as a foreign language in Afghanistan. It is the only foreign language, which is taught as a required course at schools and universities (Orfan, 2020). However, very little attention is paid to figurative language especially idioms in English classes both at the university level and in English language centers.…”
Section: Introductionmentioning
confidence: 99%
“…However, a study from Berowa et al (2018) exploring Vietnamese university students studying in the Philippines did not find gender differences in the students' attitudes. Similar findings were also obtained in a recent study by Orfan (2020) in Afghanistan. Meanwhile, in Thailand, Hayes (2014) examined the value of learning English among university students in Thailand and noted that the students embraced the notion of English as a tool for personal economic advancement; nevertheless, gender differences in the attitudes toward English learning are still insufficiently researched in Thailand.…”
Section: Attitudes and Gendersupporting
confidence: 91%
“…Applicants of master's and doctoral programs in public universities are required to pass an English proficiency test otherwise they are not allowed to participate in the specialized test. Certification of instructors' English proficiency by an accredited English body is required for promotion (Orfan & Noori, 2021;Orfan, 2020b).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the Afghan Ministry of Higher education has required translation of a book from an international language to a national language for promotion from a particular academic rank to another one. Most of the Instructors prefer to translate an English book into one of the national languages (Orfan, 2020b). In addition, English is important in Afghan economy and social media.…”
Section: Introductionmentioning
confidence: 99%